A comparison of left ventricular abnormalities associated with glucose intolerance in African Caribbeans and Europeans in the UK. Issue 6 (1st June 2001) - Chaturvedi, N; McKeigue, P M; Marmot, M G; Nihoyannopoulos, P
Abstract : OBJECTIVE: To determine whether abnormalities of the left ventricle differ by glucose tolerance status, to explore reasons for differences, and to assess ethnic differences in these relations. DESIGN: Population based prevalence study. SETTING: London, UK. PATIENTS: 1152 African Caribbeans and Europeans. METHODS: Echocardiograms, blood pressure, obesity, fasting and two hour blood glucose, insulin and lipids, and urinary albumin excretion rate were measured. MAIN OUTCOME MEASURES: Left ventricular mass index, wall thickness, and early (E) to atrial (A) wave ratio. RESULTS: Left ventricular mass index was greater in diabetic Europeans than in normoglycaemic Europeans (mean (SE), 95.6 (5.0) v 79.7 (0.8) g/m 2, p = 0.001) and in diabetic African Caribbeans than in normoglycaemic African Caribbeans (88.6 (2.5) v 82.4 (0.9) g/m 2, p = 0.02). Similar, but weaker associations were observed for the E:A ratio. β Coefficients between left ventricular mass index and fasting glucose in the normoglycaemic range, adjusted for age and sex, were 2.43 in Europeans (p = 0.05) and 3.74 in African Caribbeans (p = 0.02). These were attenuated to 1.19 (p = 0.4) and 3.03 (p = 0.08) in Europeans and African Caribbeans, respectively, when adjusted further for blood pressure and obesity. Adjustments for other risk factors made little difference to the coefficients. There were no ethnic differences in risk factor relations. CONCLUSIONS: Abnormalities of the left ventricle occur in response to glucose intolerance and are observable into the normoglycaemic range. These disturbances are largely accounted for by associated obesity and hypertension. African Caribbeans have a greater degree of left ventricular structural impairment, emphasising the importance of tight blood pressure control.